The Effect Of Perceived Risk, Brand Image And Perceived Price Fairness On Customer Satisfaction - Innocentius Bernarto; Agus Purwanto; Ronnie Resdianto Masman (Jurnal Manajemen, 2022)
This study aims to analyze the effect of perceived risk, brand image and perceived price fairness on customer satisfaction at Japanese restaurants in Jakarta, Indonesia. The target population of this research was all Japanese restaurant customers in Jakarta and its surroundings during the period of October 2021. There was a total of 208 respondents participated in this study. The sampling technique used was snowball sampling. The data was collected using a questionnaire distributed online through Google Form. The data were analyzed using the partial least square-structural equation modelling (PLS-SEM) approach in WarpPls 7.0 program. The results show that the perceived risk has no negative effect on customer satisfaction. The brand image also has a positive effect on customer satisfaction. The perceived price fairness has a positive effect on customer satisfaction. The more affordable the price of Japanese restaurant food products, the higher the customer satisfaction.